Protein modulation of ion channels - Cloake, AM (2021)
Ion channels lie at the heart of electrical excitability. They represent attractive targets for treatments of a range of pathophysiological conditions, including pain, ischemia and epilepsy. To date, small molecule approaches have dominated ion channel drug discovery, but small molecules often lack the appropriate safety and specificity, ultimately leading to their rejection in the clinic. One way in which to overcome this is to use proteins which use large molecular scaffolds to very precisely place a few key residues in order to modulate ion channel function. To this end, we characterise α-scorpion toxin binding to Nav channels, showing α-scorpion toxin AahII binds to VSDIV and inhibits upward voltage sensor movement. We interrogate the pharmacology of these naturally occurring toxins and probe electrochemical coupling involved in the fast-inactivation process of Nav channels which was uncovered in our work, in order to gain insights into the gating cycle of the channels. Better understanding of this process may allow development of novel therapeutics targeting inactivated Nav channels. Additionally, we characterise VHH domain antibody binding to K2P channels, showing they are capable of both activation and inhibition of channel activity and show high selectivity towards their target. We postulate a mechanism of action through the external pH-sensing pathway and show their activity on rodent channels, uncovering analgesic potential. Additionally, we develop the VHH antibodies as tools to allow visualisation of TREK-2 in native cells, showing selective binding against their target over closely related channels and provide some preliminary data to show localisation of TREK-2 within neurons of rat sympathetic cervical ganglia but not in the glial cells, consistent with RNA-seq data.